2019
DOI: 10.7717/peerj.7000
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nasal irrigation devices: a Thai multicentre survey

Abstract: Background Nasal irrigation is widely used as an adjunctive treatment for nasal diseases. There is little evidence regarding the efficacy of the devices used in this procedure. The objective of this survey was to evaluate the effectiveness of nasal irrigation devices based on the experiences of patients and physicians. Methods We conducted a multicentre survey study between November 2017 and October 2018. Physician and patient questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…(2) Neither is there evidence that nasal rinse would lead to worsening olfaction. Nasal saline irrigation has no effect on normal olfaction [151], and its use in nasal disease has not led to adverse outcome [152]. Its hydrating effect may possibly help to prevent and overcome dry nose during COVID-19 [153].…”
Section: Discussionmentioning
confidence: 99%
“…(2) Neither is there evidence that nasal rinse would lead to worsening olfaction. Nasal saline irrigation has no effect on normal olfaction [151], and its use in nasal disease has not led to adverse outcome [152]. Its hydrating effect may possibly help to prevent and overcome dry nose during COVID-19 [153].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the VAS score was correlated with the Sino‐nasal Outcome Test (SNOT‐22) 18,19 . The construct validity of this questionnaire was shown in our previous study 11 …”
Section: Methodsmentioning
confidence: 62%
“…12 We also found a trend toward significance favoring high-volume, high-pressure devices for rhinosinusitis from the subgroup analysis. 11 To confirm this trend, the current study expands upon our previous research by examining the comparative effectiveness of various nasal irrigation devices in rhinosinusitis based on patient experience.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the Thai community screening program for ear nose and throat diseases, the prevalence of allergic rhinitis diagnosed by the otolaryngologists ranging from 3 to 5% 3‐7 . The main treatment options for allergic rhinitis include antihistamines, intranasal corticosteroids, and nasal irrigation 1,8 …”
Section: Introductionmentioning
confidence: 99%